Ethno Botanical Edible Plant Biodiversity of Lepcha Tribes - Kumar, Ashok; Avasthe, R. K.; Shukla, Gopal; Pradhan, Y. (Indian Forester, 2012)
Dzongu area of North Sikkim is one of the most biologically diverse habitats reserved for the Lepcha tribe in Sikkim. Surveys were conducted among the community during January to December 2009-10 to document the edible plants wealth of the area. Edible resources were categorized into four types on the basis of their uses. The paper highlights the edible resources commonly used by these tribes for life saving purposes in a very remote part of the country. Among vegetables, spices, fruits and underutilized plants, 38 plants belonging to 11 families under 24 genera are used as vegetables, nine plants from five families and seven genera are used as spices, 10 plants from seven families and nine genera are used as fruits and 19 plants from 17 families and 18 genera are underutilized for different purposes.